Relation of serum S-100 protein to infarct size and clinical prognosis - (:unkn) unknown (My University, 2004)
Objectives: To analyze serum concentrations of S-100 protein in acute ischemic stroke and to determine its correlation to infarct size and clinical prognosis. Methods: Serum samples were collected from 26 acute ischemic stroke patients on admission and on the third and seventh days. Serum S-100 protein levels were measured using Smart S-100 protein detection reagent. The lesions were classified as supratentorial middle cerebral artery infarctions and infratentorial brainstem infarctions. All patients had cranial computerized tomography (CT) scan in the first 24 hours and magnetic resonance imaging (MRI) or CT scan in the first week. Neurological evaluation was made with the National Institute of Health Stroke Scale (NIHSS) in the acute stage and with Modified Barthel Index (MBI) in the 1st and 6th months. ANOVA was used for statistical analysis. Results: MCA infarctions greater than 2/3 of MCA territory had highest S100 protein levels on day 3, greater scores on NIHSS and smaller scores on MBI. Serum S-100 was undetectable in the infratentorial infarction group. Conclusion: S-100 protein is correlated with the infarct size and prognosis in MCA lesions and its rise on the 3rd day may reflect edema.
Keywords: Iinfarct size; Ischemic stroke; Prognosis; S-100 protein